Juridical Review Of Default In A Motorcylcle Leasing Agreement (Research Study At. PT Adira Dinamika Multifinance, Tbk) - Yosphi Kaena (Journal of Law Science, 2022)
Development in a society is seen in the development of existing institutions in that society, both in the economic, social, cultural and political fields. In line with the increasing number of National Development activities, the participation of the private sector in the implementation of development will also be increased. This situation, either directly or indirectly, will demand more active activities in the financing sector. Various efforts to raise public funds have been made through the establishment of government policies. Business expansion requires financing of funds, apart from the banking system and non-bank financial institutions that are known, there are other alternative financing systems, namely: "leasing. Basically the agreement that has been made applies as a law for the parties as stated in article 1338 of the Civil Code. However, in reality, it is not uncommon for the parties to carry out the agreement that has been made, which is known as "default". Such is the case in the leasing agreement. The occurrence of congestion in the payment system, violations of the provisions in the leasing contract such as sub-leasing, pledging goods that are the object of the lease or selling the goods with the aim of breaking away from rental payments are examples of forms of default committed by the lessee. This is what ultimately causes execution by the lessor of the leasing object.